Avaliação da eficácia terapêutica do cetorolaco trometamol em pacientes com disfunção temporomandibular - Linhares, José Henrique (2021)
The International Association for the Study of Pain (IASP), understands pain as "an unpleasant sensitive and emotional experience associated with, or similar to that associated with, a real or potential tissue injury". Temporomandibular disorders (TMD) encompass a group of musculoskeletal and neuromuscular conditions involving the temporomandibular joints (TMJ), masticatory muscles, and all associated tissues. The aim of this study was to evaluate the therapeutic efficacy of Ketorolac Trometamol (a 10mg sublingual tablet, every 8 hours, for five days) in reducing the impact of pain, in increasing the TMJ joint amplitude, in quality of life, in improving sleep quality and depression symptoms in patients with TMD. The study is a prospective double blind, placebo-controlled, randomized, parallel clinical trial, developed at the Faculty of Dentistry - Campus Sobral - UFC and at the Physical Rehabilitation Center, which followed the ethical standards for clinical studies, according to Resolution No. 466/2012 of the CNS, approved at CEP/UFC and published in the Brazilian Registry of Clinical Trials. The results showed a studied population corresponding to the recruitment of 198 patients who sought treatment for orofacial pain, of these 179 were excluded, 19 included (randomized into two groups) and 02 removed during the study. There were statistically significant diferences (P<0.0001) in the improvement of quality of life, sleep and depression levels, compared to the placebo group and compared between the two groups. There were no statistically significant improvements in the global assessments of pain intensity (P=0.3582), from pain threshold to pressure in the regions of: temporal muscle (P=0.5249); masseter muscle (P=0.2838); ATM (P=0.5961); and neither the range of mouth opening: active without pain (P=0.8338); maximum active (P=0.8750); maximum passive (P=0.9455), in patients with TMD treated with Placebo and Ketorolac in the measurements made in visits V0 (pre-treatment), V1, V2, V3 and V4 (post-treatment). It is concluded that the therapy of Cetorolaco Trometamol was safe and effective in improving the quality of life, sleep and depression levels of patients with TMD.